2020
DOI: 10.3390/cancers12123796
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Ablation Versus Radiofrequency Ablation for Treatment of Hepatocellular Carcinoma: A Meta-Analysis of Randomized Controlled Trials

Abstract: There are limited and discordant results on the comparison between microwave ablation (MWA) and radiofrequency ablation (RFA) for the treatment of hepatocellular carcinoma (HCC). This meta-analysis aims to compare the two treatments in terms of efficacy and safety, based on a meta-analysis of randomized-controlled trials (RCTs). A computerized bibliographic search was performed on the main databases throughout August 2020. The primary outcome was the complete response rate, while survival rate (at 1-, 2-, 3-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 29 publications
7
54
0
Order By: Relevance
“…Meanwhile, PMCT can overcome the "heat sink effect" which is an obvious disadvantage of RFA (32). A Meta-Analysis of randomized controlled trials indicated a similar efficacy and safety profile between PMCT and RFA, however, distant recurrence rate was significantly lower with PMCT (RR=0.60, 0.39-0.92) in comparison with RFA (8). In China, more than 80% of HCC patients are associated with varied degrees of liver cirrhosis (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, PMCT can overcome the "heat sink effect" which is an obvious disadvantage of RFA (32). A Meta-Analysis of randomized controlled trials indicated a similar efficacy and safety profile between PMCT and RFA, however, distant recurrence rate was significantly lower with PMCT (RR=0.60, 0.39-0.92) in comparison with RFA (8). In China, more than 80% of HCC patients are associated with varied degrees of liver cirrhosis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LR is still widely considered as the first option for the treatment of HCC patients without cirrhosis or Child-Pugh class A cirrhosis without portal hypertension (PH) (3,5). In recent years, local ablations (LA), such as percutaneous microwave coagulation therapy(PMCT) and radiofrequency ablation (RFA), have been recommended as the first-line therapeutic options for patients with early-stage HCC and PMCT seems to show some advantages over RFA regarding efficacy, including better tumor control for perivascular HCCs, and better necrosis rate for cirrhotic liver (6)(7)(8). LR may sacrifice additional normal liver tissue which is critical for those with advanced liver cirrhosis, and may lead to severe surgical complications, such as liver failure (9).…”
Section: Introductionmentioning
confidence: 99%
“…Subgroup analysis showed no difference in median OS between RFA (28.4 months) and MWA (24.4 months) groups. In liver, no difference was observed in terms of local efficacy between RFA and MWA, although long-term recurrence seemed lower with MWA [92].…”
Section: Local Efficacy and Predictors Of Recurrencementioning
confidence: 77%
“…Moreover, percutaneous TA treatment in this study included two methods: RFA and microwave ablation. However, many studies have indicated a similar efficacy and safety profile exists for these two techniques [27,28]. Finally, combination therapy has been a hot topic in recent years.…”
Section: Discussionmentioning
confidence: 99%